2020
DOI: 10.1007/s10616-019-00358-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-125a-3p participates in odontoblastic differentiation of dental pulp stem cells by targeting Fyn

Abstract: Fyn is a member of the protein tyrosine kinase family and its overexpression is associated with various types of inflammation. MicroRNAs can regulate the expression of target genes and play an important role in varied physiological and pathological processes. Based on the important role of Fyn and microRNA-125a-3p (miR-125a-3p) in inflammation, and combined with the bioinformatics studies, we performed in this study and chose miR-125a-3p as the focus of our research. During the progression of inflammation, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Besides, DPSCs treated with TNF- α exhibit increased expression of Fyn, a member of the protein tyrosine kinase Src family, which is related to inflammation and odontogenesis; however, the expression of miR-125a-3p is decreased. It has been found that miR-125-3p can reverse the inflammatory response and enhance odontogenic differentiation by repressing Fyn [ 169 ]. Moreover, a certain concentration of LPS can improve the proliferation, adhesion, and migration of DPSCs and differentiation of odontoblast through Toll-like receptor (TLR-4), ERK, and P38 MAPK signaling pathways [ 164 , 170 ].…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“…Besides, DPSCs treated with TNF- α exhibit increased expression of Fyn, a member of the protein tyrosine kinase Src family, which is related to inflammation and odontogenesis; however, the expression of miR-125a-3p is decreased. It has been found that miR-125-3p can reverse the inflammatory response and enhance odontogenic differentiation by repressing Fyn [ 169 ]. Moreover, a certain concentration of LPS can improve the proliferation, adhesion, and migration of DPSCs and differentiation of odontoblast through Toll-like receptor (TLR-4), ERK, and P38 MAPK signaling pathways [ 164 , 170 ].…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“…Increasing research and evidence have proved that anomalous levels of miRNAs are closely associated with the genesis and progression of different types of diseases, and they further regulate the biological function of various cells, including hDPSCs ( 11 , 12 ). For example, miR-125a-3p is found to have the ability to regulate the odontoblastic differentiation of hDPSCs by targeting Fyn ( 13 ). Low-expression of miR-224-5p could enhance the migration and proliferation of hDPSCs ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fyn is a member of the protein tyrosine kinase Src family, and its overexpression is associated with inflammation and odontogenesis [94]. These findings suggest that the induction of miR-125b overexpression in pulpal inflammation can reverse the inflammatory response and improve odontogenic differentiation, through the repression of Fyn [94,136].…”
Section: Mir-125bmentioning
confidence: 94%
“…About the role of miR-125a and miR-125b in pulp inflammation, to date, there is no evidence of miR-125b. Regarding miR-125a, there is only one study in which it was observed that the stimulation of DPSCs with TNF-α induces the downregulation of the expression of miR-125b, while the expression of Fyn was upregulated [136]. Fyn is a member of the protein tyrosine kinase Src family, and its overexpression is associated with inflammation and odontogenesis [94].…”
Section: Mir-125bmentioning
confidence: 99%